OPTIMASI UNJUK KERJA KINCIR AIR UNDERSHOT - Agato Agato; Alfesius sunarso Sunarso; Narsih Narsih; Dominikus Sulistiono Domi; Dovian Iswanda (Jurnal Rekayasa Mesin, 2023)
The purpose in this research, the performance of the undershot waterwheel with hydraulic channel modifications were investigated. Testing was carried out on undershot waterwheel with diameter of 0,48 m, width of 0,10 m and the number of blades of 12. Weir of 0,24 m, length headrace of 0,1 m under flow rate of 0,105 m3/s with variations sluice openings of 0,06 to 0,12 m and flow guide of 30° to determine the torque, power and efficiency of the wheel. The larger the sluice opening, the torsional tendency, power and efficiency increased. For each opening of sluice, power and efficiency increased to the value maximum and then tend to decreased. The use of flow guide of 30° in the modification of hydraulic channel carried out in this study, had not been able to increase the output power and efficiency of the wheel.